Linguistic Features of Limbu Mundhum - Tumbahang, Mohan Kumar (JODEM: Journal of Language and Literature, 2020)
This article attempts to look into the kind of language employed in the Mundhum corpus that puts the intricacy to the Limbu natives. To analyze the linguistic aspect of the Mundhum, the study has applied linguistic devices/tools based especially on phonic feature to syntactic structure or pattern. This study, thus, is qualitative in nature and the non-numerical data were collected from the books, journals, articles and religious scripture. The analysis has revealed that the Kirat Limbu Mundhum corpus is a complicated ancient form of poetry believed to be the sacred religious scripture. It has distinctly different language variety in terms of orthographic, phonological, sematic, syntactic and above all the stylistic feature. The linguistic deviation in the Mundhum has set itself off the ordinary language variety causing obscurity for a larger number of the Limbu native speakers. Obsolete and classical terminologies stand as a stumbling block and that have added more obscurity even to the most Limbu natives. The article can be beneficial for those researchers who have a desire to study the classical languages like the Kirat Limbu Mundhum.